Characteristics and Predictors of HCAHPS Nonresponse After Spine Surgery. Issue 8 (15th April 2020) - Malpani, Rohil; Adrados, Murillo; Mercier, Michael R.; McLynn, Ryan P.; Galivanche, Anoop R.; Pathak, Neil; Grauer, Jonathan N.
Abstract : Study Design: Retrospective cohort study. Objective: To assess nonresponder biases for the HCAHPS survey following spine surgery. Summary of Background Data: The Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey is a publicly reported patient satisfaction survey. In addition to having the potential of impacting a hospital's reputation, it is directly linked to government reimbursement. However, it is known that a minority of patients return this survey, and it is expected that there are nonresponder biases. Methods: All adult inpatient spine surgery patients at a single institution between January 2013 and August 2017 at a single institution were selected for retrospective analysis. Patient demographics and perioperative outcomes were assessed as potential predictors of not returning HCAHPS surveys. Univariate and multivariate analyses were performed. Results: Of 5517 spine surgeries analyzed, 1505 (27.3%) patients returned the HCAHPS survey. Response rate was variable based on patient characteristics (with statistically significant differences based on age, functional status, race, and American Society of Anesthesiologists score) but not variable based on anatomic region of the spine surgery. Multivariate analysis revealed that patients who did not return the HCAHPS survey were more likely to be black/African American (OR = 2.8, P < 0.001), have a higher American Society of Anesthesiologists score (OR 1.76, P < 0.001), and have had a major adverse event (OR = 1.66; P = 0.001), minor adverse event (OR = 2.50; P < 0.001), discharged to a destination other than home (OR = 2.16, P < 0.001), hospital readmission (OR = 2.58; P < 0.001), and a long hospital length of stay (OR = 1.28, P = 0.001). Conclusion: For spine surgery patients, patient characteristics and perioperative outcomes were found to be significantly associated with the nonresponder bias for HCAHPS surveys. Although the potential resultant bias in HCAHPS scores cannot be directly determined, this must be considered in interpreting the results of such satisfaction surveys given that less than one-third of patients actually completed this survey in the study population. Level of Evidence: 3 Abstract : The Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey is a publicly reported patient satisfaction survey. Of 5517 spine surgeries at a single institution, only 27.3% of patients returned the HCAHPS survey. The rate of survey return was significantly associated with defined patient characteristics and perioperative outcomes.